2012
DOI: 10.1186/1476-511x-11-57
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of lipid stability of broiler breast meat and meat products fed on alpha lipoic acid and alpha tocopherol acetate supplemented feed

Abstract: This study was designed to investigate the effect of alpha lipoic acid (ALA) and alpha tocopherol acetate (ATA) on the antioxidant potential, lipid stability and the quality of the broiler breast meat and meat products. The treatment plan was as (T1 = control feed, T2 = 200 mg ATA + 25 mg ALA/kg feed, T3 = 200 mg ATA + 75 mg ALA/kg feed, T4 = 200 mg ATA + 150 mg ALA/kg feed, T5 = Oxidized oil (4%), T6 = 200 mg ATA + 150 mg ALA + Oxidized oil (4%)/kg feed). After two weeks of acclimatization the birds were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
7
20
0
4
Order By: Relevance
“…Supernatants were obtained and further used for antioxidant assays. Antioxidant activities of the fungi were measured by a 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging assay (Sohaib et al, 2012) and 2,2 -azino-bis(3-ethyl-benzthiazolin-6-sulfonic acid) (ABTS) method (Petacci et al, 2010).…”
Section: Assay For Antioxidant Potentials Of Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Supernatants were obtained and further used for antioxidant assays. Antioxidant activities of the fungi were measured by a 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging assay (Sohaib et al, 2012) and 2,2 -azino-bis(3-ethyl-benzthiazolin-6-sulfonic acid) (ABTS) method (Petacci et al, 2010).…”
Section: Assay For Antioxidant Potentials Of Fungimentioning
confidence: 99%
“…All biochemical assays in the serum were performed in duplicate and according to manufacturer's instructions (DiaSys Diagnostic System GmbH, Holzheim, Germany). The antioxidant activities in serum were measured by DPPH (Sohaib et al, 2012) and ABTS (Petacci et al, 2010) free-radical scavenging assay methods as mentioned above. For the entire assays in the whole blood and serum, the intra-assay and inter-assay coefficients of variation of the control samples were 1.5-4.8 and 2.7-5.4 %, respectively.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Skin color did not differ (P>0.05) between treatments. No data have been published on color measurements directly on breast meat from chickens fed ALA-supplemented diets, although color data have been reported for raw chicken meat in the form of nuggets and hamburgers (21) . In the nuggets at day 0, the control did not differ from the lowest ALA level (25 mg ALA/kg feed), which, in turn, did not differ from the other tested ALA levels.…”
Section: Dripmentioning
confidence: 99%
“…Los resultados obtenidos con la mayor dosis, 320 ppm, concuerdan con lo observado por otros autores (6,21) , quienes administraron ácido alfa lipoico junto con alfa-tocoferol y observaron que el grupo con la mayor dosis (150 mg AAL + 200 mg ATA/kg de alimento) presentó el menor peso. En este sentido los resultados de Díaz et al (8) muestran que 40 ppm de AAL en la dieta, no tuvieron efecto sobre el consumo de alimento, pero sí mejoraron la ganancia diaria de peso y la conversión alimenticia.…”
Section: Dripunclassified
“…The previous studies indicated that the use of antioxidants is one of the most important ways to enhance the antioxidant capacity and prevent lipid oxidation of animal (Jiang et al 2007). Also, there were studies showed that the supplementation of exogenous antioxidants in diet could improve the meat quality (Sohaib et al 2012).…”
Section: Introductionmentioning
confidence: 99%